The Problem of Training Social Educators to Work With Children with Special Educational Needs in Rural Mountainous Schools - Voroshchuk, Oksana; Ketsyk, Ulyana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article deals with the problem of inclusive education of children with the special educational requirements at comprehensive rural school in a mountainous region. The author indicates that the special system of inclusive education for such students at rural schools is important at present time. The results of questionnaire of parents as to their knowledge about inclusive education are shown. Social teachers who work at rural schools in a mountainous region should conduct informatively-elucidative work among parents with the aim of support of vital functions of school, improvement of understanding and communication of all students of school, taking into account the special educational necessities of separate students, and also give an opportunity to the children with the special educational necessities to get such a social experience as well as their healthy friends.